Soziale Dimensionen von Hitzebelastung in Grossstädten. - (:unkn) unknown (Routledge, 2012)
Increasing heat stress is one of the impacts of global warming cities have to cope with and adapt to. The recent German and international debate focuses on the threat of increasing mortality rates, especially the vulnerability of the elderly people and measures to reduce it. Further, possibilities of adaptation to climate change by means of urban design to reduce the urban heat island effect are investigated. Little is known so far about the subjective perception of heat stress of different social and demographic groups, about how heat stress interferes with everyday life conduction of the inhabitants of cities, about subjective adaptation strategies and thus, about the interrelation of heat stress and the organization of the urban society. Building on two recent exploratory studies, the paper shows what other dimensions of heat stress are relevant too. The results give rise to a number of hypotheses on the social dimensions of heat stress that have to be further investigated.
Social dismensions of heat-stress in cities.
Keywords: Umwelt; Verdichtungsraum; Großstadt; Klima; Wärme; Behaglichkeit; Klimaanpassung; Anpassungsforschung; Empfindung; Hitzebelastung